We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
300
2
avatar

4(x+7)^2=1

 Mar 20, 2018
 #1
avatar+211 
+2

4 (x+7)^2 = 1

 

4x^2 + 56x + 196 = 1       Simplifying the equatation

4x2 + 56x + 195 = 0        Subtracting 1

(2x + 13) (2x + 15) = 0    Factorizing the left side

 

2x + 13 = 0   and   2x + 15 = 0

x = -13/2   or   x = -15/2

 Mar 20, 2018
 #2
avatar+7616 
+1

Here is another way:

 

4(x + 7)2   =   1

                               Divide both sides of the equation by  4 .

(x + 7)2   =   1/4

                               Take the ± square  root of both sides.

x + 7   =   ±√[ 1/4 ]

 

x + 7   =   ±1/2

                               Subtract  7  from both sides.

x   =   ±1/2 - 7

 

x  =  1/2 - 7            or          x  =  -1/2 - 7

x  =  1/2 - 14/2       or          x  =  -1/2 - 14/2

x  =  -13/2              or          x  =  -14/2

 Mar 20, 2018

4 Online Users